PENGARUH KINERJA CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP PERSISTENSI LABA PADA PERUSAHAAN YANG BERGERAK DI SEKTOR INDUSTRI DASAR DAN KIMIA DI INDONESIA - Shannon Dorothy Tedjosukmono (Business Accounting Review, 2016)
The successful implementation of Corporate Social Responsibility (CSR) is less precise when measured with periodic financial performance, therefore it is more appropriate to measure it by using earning persistence as the measure of sustainable performance. However, researches linking CSR to earning persistence is still very rare. Therefore, this study was conducted to determine the influence of Corporate Social Responsibility (CSR) to the earning persistence on companies of basic and chemical industry listed on the Stock Exchange in Indonesia in 2010 until 2014 with 88 samples and the use of SPSS version 22 as a measuring tool.This research has CSR as independent variable and earning persistence as the dependent variable. Operating cycle, sales volatility, cash flow volatility and negative earning were used as control variables. The results of this research has not been able to prove the impact of CSR on earning persistence of companies on basic and chemical industry in Indonesia. The control variables used in this research also have not been able to prove their impact on the persistence of earnings of companies on basic and chemical industry in Indonesia.